The value of urinary uric acid and creatinine ratio in neonatal asphyxia - Dr. Nikhil Gupta; Dr. Alka Bhambri; Dr. Vedika A Bhat; Dr. Rashmi Katyal; Dr. Shikha Saxena; Dr. Shashank Mishra (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: The value of urinary uric acid and creatinine ratio in neonatal asphyxia. Method: This was a prospective observational study conducted over one year, on 45 newborns admitted in NICU with perinatal asphyxia. Cord blood from the umbilical artery was sent for pH analysis and urinary uric acid and creatinine levels were estimated in spot urine samples. Results: The urinary uric acid and creatinine ratio had a positive correlation with low APGAR scores at the 1st and 5th minute. Also, urinary uric acid to creatinine ratios was significantly higher in infants with severe HIE (3.180.61) when compared with infants of moderate HIE (2.190.32). It showed a significant negative correlation with pH of cord blood in neonates with perinatal asphyxia. Conclusion: The urinary uric acid and creatinine ratio can be used as a supportive diagnostic test for early diagnosis of perinatal asphyxia.